Step Number and Aerobic Minute Exercise Prescription and Progression in Stroke: A Roadmap. (February 2022) - Peters, Sue; Klassen, Tara; Schneeberg, Amy; Dukelow, Sean; Bayley, Mark; Hill, Michael; Pooyania, Sepideh; Yao, Jennifer; Eng, Janice
Background: While higher therapeutic intensity improves motor recovery after stroke, translating findings from successful studies is challenging without clear exercise intensity targets. We show in the DOSE trial 1 more than double the steps and aerobic minutes within a session can be achieved compared with usual care and translates to improved long-term walking outcomes. Objective: We modeled data from this successful higher intensity multi-site RCT to develop targets for prescribing and progressing exercise for varying levels of walking impairment after stroke. Methods: In twenty-five individuals in inpatient rehabilitation, twenty sessions were monitored for a total of 500 one-hour physical therapy sessions. For the 500 sessions, step number and aerobic minute progression were modeled using linear mixed effects regression. Using formulas from the linear mixed effects regression, targets were calculated. Results: The model for step number included session number and baseline walking speed, and for aerobic minutes, session number and age. For steps, there was an increase of 73 steps per session. With baseline walking speed, for every 0.1 m/s increase, a corresponding increase of 302 steps was predicted. For aerobic minutes, there was an increase of .56 minutes of aerobic activity (ie, 34 seconds) per session. For every year increase in age, a decrease of .39 minutes (ie, 23 seconds) was predicted. Conclusions: Using data associated with better walking outcomes, we provide step number and aerobic minute targets that future studies can cross-validate. As walking speed and age are collected at admission, these models allow for uptake of routine measurement of therapeutic intensity. Registration:www.clinicaltrials.gov ; NCT01915368.